The Effect Of Fast Front Impulse Waveshape Upon The Electrical Transformator Distribution Voltage - Perpustakaan UGM, i-lib ([Yogyakarta] : Universitas Gadjah Mada, 1998)
The invention of vacuum circuit breaker enables to switch on an electrical circuit in a very fast time due to short gap between the circuit breaker contacts. This means that the voltage applied to the electrical circuit has a very steep front time or contains high frequency components Electrical transformator winding is simulated by an inductor having nine taps representing distributed sections of an electrical transformator winding. The very fast front time of voltage produced by a low voltage recurrent surge generator is applied to the inductor. The results of this investigation reveal that the steeper the front time of an impulse waveshape of voltage applied to the transformator causes the more voltage stress to the part of winding closest to the line terminal.